2019
DOI: 10.1055/s-0039-1694747
|View full text |Cite
|
Sign up to set email alerts
|

A Clinician's Approach to Peripheral Neuropathy

Abstract: Peripheral neuropathies are a group of disorders that affect the peripheral nervous system, for which hundreds of etiologies have been identified. This article presents a stepwise approach to the evaluation and workup of peripheral neuropathy, which starts with a detailed history of symptoms, family and occupational history, and a neurological as well as general physical exam. Pattern recognition of various neuropathies can help to build a differential diagnosis based on the presentation. Such patterns include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 87 publications
0
57
1
4
Order By: Relevance
“…1 The common pattern of neuropathy of the PNS includes traumatic rupture or avulsion, external compression, viral infection related neuritis, or neurogenic tumor formation. 2,3 When it comes to PNS reconstruction, motor nerve reconstruction is the most commonly encountered; this includes brachial plexus reconstruction, facial reanimation, and extremity reconstruction. 4 Nerve reconstruction is most commonly performed by reinnervating the denervated muscles by coapting the motor nerve in the acute stage, or palliative reconstruction with functioning free muscle transplantation or tendon transfers in chronic stage.…”
mentioning
confidence: 99%
“…1 The common pattern of neuropathy of the PNS includes traumatic rupture or avulsion, external compression, viral infection related neuritis, or neurogenic tumor formation. 2,3 When it comes to PNS reconstruction, motor nerve reconstruction is the most commonly encountered; this includes brachial plexus reconstruction, facial reanimation, and extremity reconstruction. 4 Nerve reconstruction is most commonly performed by reinnervating the denervated muscles by coapting the motor nerve in the acute stage, or palliative reconstruction with functioning free muscle transplantation or tendon transfers in chronic stage.…”
mentioning
confidence: 99%
“…Always clinical examination should be followed by electrophysiology if neuropathy is suspected. 13 14 Electrophysiology is indicated for workup of all cases of peripheral neuropathy after a very basic hematological and biochemical workup. Hence, it is indicated in all leprosy suspects and patients, because in all leprosy cases, there is subclinical neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…It was mosaic pattern of 68% demyelinating and 36% axonal with overlap. 13 Electrophysiological abnormalities reported were reduced amplitude of motor and sensory potential (axonopathy) or prolonged latencies and slowing of conduction velocity (demyelination). 7 8 Different authors have found varying pattern of neurophysiological abnormalities in leprous neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Diphtheria and certain toxic neuropathies (amiodarone) are among rare causes. 75 Acute axonal neuropathies may result from porphyria, critical illness neuromyopathy, vasculitis, infection, and certain variants of GBS. 75 3A.…”
Section: Immune-mediated Necrotizing Myopathies (Imnm)mentioning
confidence: 99%